Gestão de processos em uma empresa do setor elétrico - Madiolo, Adriana de Souza; Morishita, Cristiane Sayuri; Lizarelli, Fabiane Letícia; Martins, Manoel Fernando; Ito, Maurício Antonio Oliveira (Revista Gestão da Produção Operações e Sistemas, 2006)
This paper states the concepts of process. A process is defined as a succession of activities, each activity has input, like materials, information and knowledge and its outputs are activities results. A process map is logical and ordered succession of these activities, then, is possible to see the process flows (material or information flow) inside a company. This article intends to show a real situation of study, to describe how the concept of business process works inside a service company. Through this study the company re-designed their process searching a better way to manage the activities. As a study result the employees improve the understanding about the company and the process. Key words: Process, Case study, Managing by process.